Implementasi Algoritme SPECK Pada Fuzzy Keyword Search Dalam Network Storage - Syahmi Rifqi Hudha Perwira; Ari Kusyanti; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The advantage of using network storage is users can access data easily and network storage will provide storage with unlimited capacity. However, there is a lack of data privacy and confidentiality in network storage and also there is possibility of internal attacks and external attacks if the data stored is not encrypted. SQL injection is one of them, SQL injection is used to get additional information by accessing the SQL console. Therefore, the stored data must be encrypted in order to overcome the attack. One of the ways to secure this data is to apply the SPECK algorithm to ensure data confidentiality. The SPECK algorithm is applied to securing files and data in the database. Tests that carried out in this study are test vector validation, system functionality, system non-functionality, active attack system security test, passive attack system security test and encryption and decryption validation. Test vector result from system is matched with the ciphertext result obtained from the journal, using input such as plaintext and key that also obtained from the journal.